Obtenção de extratos de folhas de Moringa oleifera por ultrassom e aplicação no tratamento de sementes de tomate-cereja - Bechlin, Taise Raquel (2023)
Moringa oleifera leaves are composed of substances with antioxidant and antimicrobial potential, in addition to the leaves having excellent nutritional properties. In this regard, the current work focused on the optimization of the M. oleifera leaf extraction procedure aided by ultrasound and the use of the extracts as a bio-stimulant in the treatment of cherry tomato seeds. Thus, the optimized extraction process of M. oleifera leaves was carried out in terms of yield, phenolic, and flavonoid content and antioxidant activity, obtaining the following optimal operating conditions: ethanol concentration of 75% (v/v), temperature of 54.0 °C, and amplitude of 78%. The extracts obtained in the optimized condition presented values, yield, DPPH, FRAP, TPC, and TFC of 28.48%, 110.20 μgGAE g-1 , 1496.36 μmol Fe(II)SE g-1 , 473.11 μgGAE g-1 , and 128.39 μgGAE g-1 , respectively. Likewise , it works well against pathogenic mycelial growth. The maximum percentages of inhibition against Aspergillus flavus and Penicillium italicum were found at 2.0 mg mL-1 (50.47 2.60%) and 5.0 mg mL-1 (59.67 6.20%), respectively. The existence of substances like isoquercitrin and α-tocopherol, which have a high antioxidant load and are identified by GC-MS analysis, can explain the consequences of this biological activity. The leaf extracts were further assessed for their potential as a bio-stimulant for the treatment of cherry tomato seeds. Initial seed germination inhibition employing extracts at a dosage of 0.5-5.0 mg mL 1 was the main outcome. However, the 2.0 mg mL-1 dose was found to be helpful for seedling growth up to 14 days, resulting in longer roots and aerial parts compared to the control. The M. oleifera leaf extracts include bioactive compounds that have the potential to boost vegetable seedling formation and may even aid in the prevention of severities brought on by post-harvest fungus.